Why stay despite intimate partner violence? Lived experiences of victims in positions of strength - Solly Matshonis Seeletse (Humanitas: Indonesian Psychological Journal, 2024)
Intimate partner violence is a problem in every country worldwide, including South Africa. This qualitative study aimed to gather insights into the lived experiences of victims of intimate partner violence, who were the financial providers in their families and the more stable in terms of careers but remained in the relationships for prolonged periods. Five face-to-face interviews were conducted with individual participants from Pretoria township communities in the Gauteng Province of South Africa. The interviews were transcribed verbatim and then analyzed using the thematic content analysis. The themes generated from the victims’ lived experiences explain their disempowerment. The themes that emerged were the aggressor being untouchable, fear for one’s life, feeling helpless, desperate and vulnerable, self-blame, and being trapped in the relationship. The experience of being abused, especially by a completely weaker partner, was shattered and associated with a helpless life during the relationship. Therefore, the victims of intimate partner violence need exposure beyond the police and guidance in social work services that can help them seek alternative ways to escape intimate partner violence. People need to be empowered to have courage, to be brave, to have knowledge about resourceful institutions, and to be independent.